Role of skin-homing t-cells in recurrent episodes of atopic dermatitis: a review - Guo, Huimin; Yuan, Huimin; Yu, Yanru; Sun, Jingwei; Sun, Yan; Tang, Yang; Zheng, Fengjie (Frontiers in Immunology, 2025)
Atopic dermatitis (AD) is a chronic relapsing disease with complex pathogenesis. Among them, inflammation is one of the primary pathogenesis of AD. AD is characterized by infiltration of lymphocytes into the skin’s dermis, and the skin homing of lymphocytes plays an essential role in the recurrence of AD. Currently, there is more and more evidence to support this view. This article reviews the relevant role of T lymphocyte skin-homing-related molecules in the recurrence of AD to provide a reference for the cure of AD.